Desain dan Pembuatan Cetakan Sistem Injeksi untuk Cetakan Plastik Adonan Donat - Hadi, Syamsul; Murti, Tandya Nanda Haswari; Sayekti, Saifudin Kalih; Setiawan, Agus (INTEK: Jurnal Penelitian, 2016)
The problem lies in the length of process, it is hard tomake, and a donut shape (circle-shaped cake and hollow in the middle) are not good made by the domestic industry that created manually (by hand). The purpose of the design and manufacture of plastic mold injection molding system for donuts is to speed up the processing of dough donut with easy and efficient way. Methods of design and manufacture of plastic molding dough donut capacity of 30 product/hour with injection system include: survey for dimensions of donuts on the market, determining the thermal expansion of the dough after frying for the determination of shrinkage in the dimensions of the mold, mold design on the top and bottom, the design of cooling systems, the design for ejection system for mold products, working drawings, machining components, assembly, testing, and the calculation of production costs. The results of the design and manufacture of plastic molding dough donut is a donut molds for parts of the top and bottom made of plastic material types of polypropylene (PP).